Microencapsulated Pomegranate Juice Reduces Metabolic Syndrome (MetS) Criteria in Wistar Rats with MetS Induced with 30% Sucrose - José Antonio Guerrero-Solano; Juan Carlos Cancino-Díaz; Osmar Antonio Jaramillo-Morales; Mirandeli Bautista; Juan Pablo Hernández-Uribe; José Moisés Talamantes-Gómez; Carmen Valadez-Vega; Helen Belefant-Miller; Gabriel Betanzos-Cabrera (Applied Sciences)
Pomegranate juice possesses therapeutic properties against metabolic syndrome. Microencapsulation of pomegranate juice (MPJ) may extend its shelf life; however, further research is necessary to ascertain its comparative efficacy with fresh juice. This work evaluated the effect of MPJ in an animal model with induced metabolic syndrome (MetS). MetS was induced in Male Wistar rats by administering 30% sucrose orally for 22 weeks. Once MetS was verified in the animals, seven groups were formed as follows: control (Ctrl); MetS; MetS + Placebo; Ctrl + MPJ; MetS + MPJ1 600; MetS + MPJ2 1800; and MetS + MPJ3 2900 mg/kg. Systolic and diastolic blood pressure, glucose, triglycerides, and total HDL-c levels in the MetS + MPJ groups improved significantly (p < 0.05) vs. the MetS group at the end of the study. Microencapsulation maintained the anti-metabolic-syndrome properties of pomegranate juice and could be used to control metabolic syndrome.